Utilizing Internet of Things (IoT) Technology for Supply Chain Optimization in Digital Businesses - Aksenta, Almasari (Penelitian dan Pengembangan Ilmu, 2024)
The implementation of the Internet of Things (IoT) in supply chains has become an increasingly important research subject in facing the dynamics of the digital era. In this research, researchers conducted a systematic literature review to investigate the impact, supporting factors, challenges, and implications of implementing IoT to increase supply chain resilience in the digital era. Researchers analyzed various relevant literature studies from international databases such as Scopus, Web of Science, and IEEE Xplore using the Systematic Literature Review method. The research results show that IoT integration at various stages of the supply chain can significantly improve resilience, through increased visibility, operational efficiency, and responsiveness to change. Factors such as senior management commitment, adequate infrastructure and technology, human resource expertise, an organizational culture open to change, and collaboration between departments and business partners have been proven to support IoT implementation. However, challenges such as high implementation costs, data security issues, integration with existing systems, resistance to change, and regulatory uncertainty also need to be overcome. The implications of this research provide practical guidance for businesses and practitioners in implementing IoT to improve supply chain resilience, while highlighting the need to invest in training, collaboration with business partners, and attention to regulatory compliance.